2021
DOI: 10.1093/conphys/coaa128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the post-release effects of capture, handling and placement of satellite telemetry devices on narwhal(Monodon monoceros)movement behaviour

Abstract: Animal-borne telemetry devices have become a popular and valuable means for studying the cryptic lives of cetaceans. Evaluating the effect of capture, handling and tagging procedures remains largely unassessed across species. Here, we examine the effect of capture, handling and tagging activities on an iconic Arctic cetacean, the narwhal (Monodon monoceros), which has previously been shown to exhibit an extreme response to extended capture and handling. Using accelerometry-derived metrics of behaviour, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 97 publications
2
32
0
Order By: Relevance
“…Supporting this explanation, offshore dispersal of white sharks coincided with a period of faster tailbeats (i.e., rapid movement), which gradually slowed to a more constant average rate, indicating a population-level recovery period (return to "baseline" tailbeat signature) of 9.7 h. This pattern and rate of TBC recovery is similar to that identified for common blacktip sharks (Carcharhinus limbatus, 9 h; Whitney et al, 2016), but longer than for tiger sharks (Galeocerdo cuvier, 4 h; Andrzejaczek et al, 2019a), potentially suggesting lower sensitivity to capture in tiger sharks (consistent with Gallagher et al, 2014). Activity level metrics such as TBC are clearly useful for enabling standardized comparisons of recovery rates both between and within species (Brivio et al, 2015;Whitney et al, 2016;Shuert et al, 2021), yet such applications amongst elasmobranchs remain rare or are limited by short post-release monitoring periods (Bullock et al, 2015;Whitney et al, 2018;Raoult et al, 2019). Despite a low sample size, we also revealed that recovery times increased as shark length decreased.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Supporting this explanation, offshore dispersal of white sharks coincided with a period of faster tailbeats (i.e., rapid movement), which gradually slowed to a more constant average rate, indicating a population-level recovery period (return to "baseline" tailbeat signature) of 9.7 h. This pattern and rate of TBC recovery is similar to that identified for common blacktip sharks (Carcharhinus limbatus, 9 h; Whitney et al, 2016), but longer than for tiger sharks (Galeocerdo cuvier, 4 h; Andrzejaczek et al, 2019a), potentially suggesting lower sensitivity to capture in tiger sharks (consistent with Gallagher et al, 2014). Activity level metrics such as TBC are clearly useful for enabling standardized comparisons of recovery rates both between and within species (Brivio et al, 2015;Whitney et al, 2016;Shuert et al, 2021), yet such applications amongst elasmobranchs remain rare or are limited by short post-release monitoring periods (Bullock et al, 2015;Whitney et al, 2018;Raoult et al, 2019). Despite a low sample size, we also revealed that recovery times increased as shark length decreased.…”
Section: Discussionsupporting
confidence: 67%
“…So far, daily diary tags have been used to reveal many aspects of aquatic animals' natural behaviors including foraging activities, cost-efficient movement strategies, and habitat use (Shepard et al, 2011;Benoit-Bird et al, 2013;Andrzejaczek et al, 2019a). By contrast, applied behavioral research on disturbances following capture in marine and terrestrial systems has mostly relied on either traditional biotelemetry, pop-up time-depth archival tags, or accelerometers (Afonso and Hazin, 2014;Rode et al, 2014;Barnes et al, 2016;Becciolini et al, 2019;Bowlby et al, 2021;Shuert et al, 2021). However, biotelemetryderived movements or depth profiles are often insufficient for resolving cryptic behavioral processes (e.g., foraging and resting) relevant to recovery, especially in aquatic systems where telemetry data are particularly intermittent and coarse (Andrzejaczek et al, 2018(Andrzejaczek et al, , 2019a.…”
Section: Introductionmentioning
confidence: 99%
“…Assessing an individuals' 'ease of tagging', that is, the number of attempts or time taken to tag, TA B L E 1 Sampling-Exposure-Receptor framework (SERF). Further details for each category and factor are provided in SI S1, and a template is available in SI S2 Predation pressure-human Stankowich (2008) could facilitate investigation of how baseline/response metrics differ (Schuert et al, 2021). Similarly, it is important to quantify responses to tagging which, in marine mammals and other taxa, have modulated subsequent responses to stressors (Miller et al, 2009;Sun et al, 2015).…”
Section: F I G U R Ementioning
confidence: 99%
“…could facilitate investigation of how baseline/response metrics differ (Schuert et al, 2021). Similarly, it is important to quantify responses to tagging which, in marine mammals and other taxa, have modulated subsequent responses to stressors (Miller et al, 2009;Sun et al, 2015).…”
Section: Short-finned Pilot Whale (Globicephala Macrorhynchus)mentioning
confidence: 99%
See 1 more Smart Citation